Hacking the thylakoid proton motive force for improved photosynthesis: modulating ion flux rates that control proton motive force partitioning into Δψ and ΔpH. (26th September 2017) - Davis, Geoffry A.; Rutherford, A. William; Kramer, David M.
Abstract : There is considerable interest in improving plant productivity by altering the dynamic responses of photosynthesis in tune with natural conditions. This is exemplified by the 'energy-dependent' form of non-photochemical quenching ( q E ), the formation and decay of which can be considerably slower than natural light fluctuations, limiting photochemical yield. In addition, we recently reported that rapidly fluctuating light can produce field recombination-induced photodamage (FRIP), where large spikes in electric field across the thylakoid membrane (Δ ψ ) induce photosystem II recombination reactions that produce damaging singlet oxygen ( 1 O2 ). Both q E and FRIP are directly linked to the thylakoid proton motive force ( pmf ), and in particular, the slow kinetics of partitioning pmf into its ΔpH and Δ ψ components. Using a series of computational simulations, we explored the possibility of 'hacking' pmf partitioning as a target for improving photosynthesis. Under a range of illumination conditions, increasing the rate of counter-ion fluxes across the thylakoid membrane should lead to more rapid dissipation of Δ ψ and formation of ΔpH. This would result in increased rates for the formation and decay of q E while resulting in a more rapid decline in the amplitudes of Δ ψ -spikes and decreasing 1 O2 production. These results suggest that ion fluxes may be a viable target for plant breeding or engineering. However, these changes also induce transient, but substantial mismatches in the ATP : NADPH output ratio as well as in the osmotic balance between the lumen and stroma, either of which may explain why evolution has not already accelerated thylakoid ion fluxes. Overall, though the model is simplified, it recapitulates many of the responses seen in vivo, while spotlighting critical aspects of the complex interactions between pmf components and photosynthetic processes. By making the programme available, we hope to enable the community of photosynthesis researchers to further explore and test specific hypotheses. This article is part of the themed issue 'Enhancing photosynthesis in crop plants: targets for improvement'.